Measurement of σ(pp→bb[bar]X) at √s=7 TeV in the forward region - Aaij, Roel; Bachmann, Sebastian; Deissenroth, Marc; Eisele, Franz; Färber, Christian; Hansmann-Menzemer, Stephanie; Krocker, Georg Alexander; Linn, Christian; Marks, Jörg; Stahl, Sascha; Uwer, Ulrich; Wandernoth, Sebastian; et al. (Physics letters, 2010)
Decays of b hadrons into final states containing a D0 meson and a muon are used to measure the bb¯ production cross-section in proton-proton collisions at a centre-of-mass energy of 7 TeV at the LHC. In the pseudorapidity interval 2<η<6 and integrated over all transverse momenta we find that the average cross-section to produce b-flavoured or b¯-flavoured hadrons is (75.3±5.4±13.0) μb.
*LHCb Collaboration: R. Aaij, S. Bachmann, M. Deissenroth, F. Eisele, C. Färber, S. Hansmann-Menzemer, G. Krocker, C. Linn, J. Marks, S. Stahl, U. Uwer, S. Wandernoth, D. Wiedner, A. Zhelezov [und 616 weitere Personen]
Im Titel steht der zweite Buchstabe b mit einem Oberstrich
Im Titel steht der Buchstabe s unter dem Wurzelsymbol
Gesehen am 14.11.2022